2003
DOI: 10.1055/s-2003-36775
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Heteroatom Bond-Forming Reactions Mediated by Cerium(IV) Ammonium Nitrate:An Overview

Abstract: C a r b o n -H e t e r o a t o m B o n d -F o r m i n g R e a c t i o n s M e d i a t e d b y C A NAbstract: As a powerful one-electron oxidant, cerium(IV) ammonium nitrate (CAN) is useful for a variety of oxidative transformations including carbon-carbon bond formation. Recent work has also demonstrated the usefulness of CAN in carbon-heteroatom bond-forming reactions. Particularly noteworthy is the effectiveness of CAN in building C-N, C-S, C-Se, C-Br, and C-I bonds. This account is aimed at creating awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(28 citation statements)
references
References 38 publications
0
27
0
1
Order By: Relevance
“…Although extensively utilized as a one-electron oxidant [84], CAN's use as a Lewis acid catalyst in CÁN bond forming reactions leading to heterocyclic compounds is somehow limited [85]. We recently observed that a simple and highly efficient procedure for conducting the Biginelli condensation reaction of aldehydes, b-ketoesters 120, urea, or thiourea 121a,b at ambient temperature involves the use of CAN as a Lewis-acid catalyst.…”
Section: Solvent-free Reactionsmentioning
confidence: 99%
“…Although extensively utilized as a one-electron oxidant [84], CAN's use as a Lewis acid catalyst in CÁN bond forming reactions leading to heterocyclic compounds is somehow limited [85]. We recently observed that a simple and highly efficient procedure for conducting the Biginelli condensation reaction of aldehydes, b-ketoesters 120, urea, or thiourea 121a,b at ambient temperature involves the use of CAN as a Lewis-acid catalyst.…”
Section: Solvent-free Reactionsmentioning
confidence: 99%
“…Cerium (IV) ammonium nitrate (CAN) is oxidants in organic synthesis [21] and also recently, it is catalyzed many of organic synthesis and transformations such as quinoxalines [22][23], polyhydroquinolines [24], 2-phenylquinazolines, Tetrahydropyridines [25] not only based on its electron transfer capacity but also with its Lewis acidic property [26]. Using of CAN has many advantages like solubility in water, easy handling, non-toxic, eco-friendly nature, high reactivity and inexpensive, good solubility in water, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The versatility of this technology has encouraged great interest in the development of novel reagents and procedures for the generation of radicals [2]. Ceric ammonium nitrate (CAN) and manganese(III) acetate have been extensively used as single electron transfer agents for the construction of C-C bonds [1][2][3][4]. Furthermore, the utility of CAN in carbonheteroatom bond forming reactions (C-N, C-S, C-Se, CBr, C-I) was demonstrated [5].…”
Section: Introductionmentioning
confidence: 99%